Incongruence in theory and practice: black English vernacular as used in society and education / Rebecca A. Campbell - A. Campbell, Rebecca (2010)
In U.S. education, Standard English is the preferred dialect. The problem of the requirement of a Standard English dialect and how it reduces opportunity for those who do not utilize it has been discussed, yet no plausible and effective solutions have been proposed. Speakers of Black English Vernacular (BEV) are especially vulnerable to this discrimination and are the subject to of this work. Educational institutions must no longer punish students for speaking BEV; a change in the educational paradigm is required. Equal marks must be provided for work that is equal even if it is expressed in a different dialect.